Molecular analysis of the ribosome recycling factor ABCE1 bound to the 30S post‐splitting complex. (17th February 2020) - Nürenberg‐Goloub, Elina; Kratzat, Hanna; Heinemann, Holger; Heuer, André; Kötter, Peter; Berninghausen, Otto; Becker, Thomas; Tampé, Robert; Beckmann, Roland
Abstract: Ribosome recycling by the twin‐ATPase ABCE1 is a key regulatory process in mRNA translation and surveillance and in ribosome‐associated protein quality control in Eukarya and Archaea. Here, we captured the archaeal 30S ribosome post‐splitting complex at 2.8 Å resolution by cryo‐electron microscopy. The structure reveals the dynamic behavior of structural motifs unique to ABCE1, which ultimately leads to ribosome splitting. More specifically, we provide molecular details on how conformational rearrangements of the iron–sulfur cluster domain and hinge regions of ABCE1 are linked to closure of its nucleotide‐binding sites. The combination of mutational and functional analyses uncovers an intricate allosteric network between the ribosome, regulatory domains of ABCE1, and its two structurally and functionally asymmetric ATP‐binding sites. Based on these data, we propose a refined model of how signals from the ribosome are integrated into the ATPase cycle of ABCE1 to orchestrate ribosome recycling. Synopsis: Cryo‐EM structure of the ribosomal post‐splitting complex reveals an intricate interaction network between the archaeal ribosome and the regulatory domains of the recycling factor ABCE1. Signals from the ribosome are integrated into the ATPase cycle of ABCE1 to orchestrate ribosome recycling. 2.8 Å cryo‐EM reconstruction of the archaeal 30S‐ABCE1 complex defines a post‐splitting complex‐specific interaction network. Conformational domain rearrangements in ABCE1 from pre‐ to post‐splitting state are linked to closure of its nucleotide‐binding sites. Mutations of conserved residues in key structural elements impair ribosome splitting by disturbing the allosteric network between the ribosome, ABCE1 regulatory domains, and ABCE1 nucleotide‐binding sites. Abstract : Cryo‐EM structures reveal how archaeal 30S ribosome transitions from pre‐ to post‐splitting state are linked to conformational domain rearrangements and the ATPase cycle of the recycling factor ABCE1.